Education in Emergencies Designing a mobile solution for the education of refugees - Carlström, Herman; Jansson, Erik; Johansson, Alice; Larsson, Filip; Lindén, Magdalena; Samuelsson, Oskar (My University, 2017)
An overwhelming number of people are currently displaced as a result of con icts and face numerous challenges in accessing education. In order to address this limited access, this project strived to determine the requirements of a mobile e-learning platform which could support the education of refugees in regions with limited internet access. The requirements were established as a result of data collection in the form of interviews with educators and students in the region. The data collection focused on Jordan as this represents both urban and camp environments. A nal design concept and software prototype were created with the speci cation in mind and tested on-site in Amman, Jordan, in order to validate the requirements. These need to consider nancial limitations, non-binary internet access and limited English literacy and are presented as a step towards a solution for supporting refugee education.
Keywords: Data- och informationsvetenskap; Computer and Information Science